STUDY OF STAKE EVALUATION MODEL IN THE INTEREST OF PROGRAM EVALUATION - Bela Janare Putra (Universitas Jabal Ghafur, 2023)
In the field of educational assessment, Stake evaluation states that the quality of the curriculum needs to be evaluated using the Stake model. By carrying out a formative evaluation and to collect various points of view in the process in detail. The research method in this case uses a descriptive qualitative method with reference to the existing literature. The results of the research itself describe various kinds of Stake evaluation models that can be used. This can provide knowledge for the movers involved in becoming executors in a program in the realm of education. Keywords: Stake Evaluation, Program Evaluation